'It's been a long haul, a big haul, but we've made it': hepatitis C virus treatment in post-transplant patients with virus recurrence: An interpretative phenomenological analysis. Issue 2 (August 2018) - Krzeczkowska, Anna; Flowers, Paul; Chouliara, Zoe; Hayes, Peter; Dickson, Adele
The lived experience of both interferon-based and new interferon-free treatments in patients with hepatitis C virus remains understudied. To explore their journey through hepatitis C virus treatment, we interviewed seven post-transplant patients with recurrent hepatitis C virus. Three themes were identified using interpretative phenomenological analysis. Participants reported an ongoing sense of ontological uncertainty characterized by lack of control over their condition and treatment. Furthermore, an apposition of scepticism and hope accompanying each stage of hepatitis C virus treatment was described. A staged approach to psychological intervention tailored to the needs of the patient and their associated 'stage' of hepatitis C virus treatment was recommended.